2014
DOI: 10.4274/jcrpe.1477
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal Unilateral Gynecomastia: Report of 2 Cases

Abstract: Prepubertal unilateral gynecomastia is an extremely rare condition. At present, its etiology and management strategy are not well known. Two unrelated prepubertal boys of ages 8 and 9 who presented with complaints of unilateral enlargement of breast tissue are reported. Physical examination, biochemical, hormonal and oncologic work-up findings were normal. Both patients were treated with peripheral liposuction successfully. Histopathological and immunohistochemical examinations showed benign fibroglandular gyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…Prepubertal gynecomastia, especially if unilateral, is extremely rare 3 and should prompt an immediate evaluation for pathological causes and possible endocrine disorders. 1,4 In our case report, gynecomastia occurred in a 12-yearold boy with external genitalia at Tanner stage 1 (testicular volume of 2 mL bilaterally) and, therefore, prepubertal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prepubertal gynecomastia, especially if unilateral, is extremely rare 3 and should prompt an immediate evaluation for pathological causes and possible endocrine disorders. 1,4 In our case report, gynecomastia occurred in a 12-yearold boy with external genitalia at Tanner stage 1 (testicular volume of 2 mL bilaterally) and, therefore, prepubertal.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is highly prevalent and often benign during the neonatal period, puberty, and in males over 50 years-old. [2][3][4] Pubertal gynecomastia is a common and usually physiological disease, and spontaneous regression occurs within one to three years. 1,5 The prevalence of pubertal gynecomastia ranges from 3.9 to 64.6% and, typically, it appears at least six months after the onset of male secondary sex characteristics, with the peak of incidence at Tanner stages 3-4 and testicular volume of 5 to 10 mL.…”
Section: Introductionmentioning
confidence: 99%
“…Authors found 100% of epithelial periductal cells positive with intense cytosolic and nuclear staining of ER. They suggest that possible local oestrogen hypersensitivity could be responsible for unilateral localization of the lesion [16]. Study limitations included the ethical point of the impossibility to compare tissue from an enlarged breast to the healthy one on the other side in unilateral cases to prove such a hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…6 Las causas más frecuentes de ginecomastia en la edad prepuberal son la administración de compuestos estrogénicos, tumores testiculares secretores de hormonas esteroideas o hCG, síndrome de exceso de aromatasa e hiperandrogenismo familiar, síndromes como Klinefelter, Carney o Peutz-Jeghers, pubertad precoz o tumores mamarios benignos, entre otros. 4 Para llegar al diagnóstico, es primordial una exhaustiva anamnesis, clave en el caso presentado, e indagar en la forma de inicio, la evolución, los síntomas asociados, locales o sistémicos, la exposición a fármacos o sustancias (tópicos o sistémicos, por parte del paciente o por convivientes), los antecedentes familiares de ginecomastia y personales de patología de base que afecte la síntesis y el metabolismo hormonal masculino. 7,9,10 La adecuada exploración física conlleva palpar la glándula con el paciente en decúbito para diferenciar la ginecomastia real de la pseudoginecomastia.…”
Section: Discussionunclassified
“…Las causas y mecanismos que influyen en la etiopatogenia de la ginecomastia en la edad pediátrica son las siguientes: 4 causa idiopática (25%), puberal (25%), exposición sistémica o farmacológica a estrógenos (20%) (Tabla 1), 5 cirrosis/malnutrición (8%), hipogonadismo primario (8%), tumoral (3%), hipogonadismo secundario (2%), alteraciones tiroideas (1,5%), insuficiencia renal (1%) o enfermedades locales, como mastitis. 5,6 Se presenta el caso de un niño con una ginecomastia de causa traumática, infrecuente en la clínica.…”
Section: Introductionunclassified